The independence of Shari`ah Board Members in islamic banking with particular reference to Malaysia and Indonesia - Hassan, Rusni; Triyanta, Agus (Hamdan Bin Mohammed e-University (HBMeU), 2013)

(untitled)
Legal enforcement relies on at least three aspects; the existing regulatory framework, the institution acting for the enforcement of such regulatory framework, and the conduct of the persons involved. Islamic banking, as a legal entity is also subject to the legal enforcement of various regulations, including Shari`ah compliance. The well being of Shari`ah compliance in Islamic banking does not solely depend on the regulations issued, but also (as the above legal theory suggests) depends on the response of the public as well as on the institution which acts to enforce such compliance. It is clear that the Shari`ah board is one of the institutions in this important circle. Hence, the discussion on the Shari`ah board as the body that is designated to cater such compliance is significant to comprehend the whole aspect of the implementation of Shari`ah compliance. The regulation of Shari`ah compliance indicates that the compliance on the product and operation of Islamic banking with the Shari`ah principles is an ultimate basis for Islamic banking. It is part and parcel of Islamic banking’s Shari`ah governance. Having said this, there must be a body responsible for the supervision towards such compliance. It is for this reason the Shari`ah board is established within an Islamic bank or conventional bank conducting Islamic banking business. Due to the faith-based nature of the Islamic banking business, the task of the Shari`ah board is much wider than just in terms of products supervision. The members of such board need to cover more comprehensive aspects than advisors in conventional banking business. In order to perform its function perfectly, the capacity of the members certainly needs enhancement. They are required to posses a deep understanding on Shari`ah principles not only in the product development, but rather in all activities of Islamic banking. It is therefore, through the robust regulations pertaining to the role, duties and responsibilities of the Shari`ah board, the challenges towards Shari`ah compliance that the bank may enccounter, could be properly responded. Presumably from the above discussion, the compliance of Islamic banks to Shari`ah principles, to a great extent, is also determined by the role of such board. Consequently, this body needs sufficient authority to enable its members to perform their functions effectively. The members also shall be given proper independence from undue influence of the board of directors and the board of management within the industry. This paper seeks to explore the independency of the Shari`ah board members in Malaysia and Indonesia, which is very practical in nature. Prior to that, the overview on the theoretical aspect will be presented to provide a clear understanding on independence of the Shari`ah board members.